(3GdYhGed GdLOjOI aj GdfMhs - (3GdLQLGfj, GdCTYQj, GdTGaYj, CHh HcQ, YHO GdbGgQ Hf YHO GdQMef Hf eMeO, (B471 (3g`s ((3eOQSI MGLj eMehO CafOj edG eMeOs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf GdYhGed aj GdfMh Ydi eG Cdag GdTjN YHO GdbGgQ Hf YHO GdQMef GdLQLGfjeGFI YGed hgj JfbSe Edi bSejf daXjI heYfhjI aGddaXjI efgG JfbSe Edi bSejf SeGYjI hbjGSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 48s
(3eYLe GdeDdajf(B: 2 / 201s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs